Stratified active archaeal communities in the sediments of Jiulong River estuary, China - Li, Qianqian; Wang, Fengping; Chen, Zhiwei; Yin, Xijie; Xiao, Xiang (Frontiers in Microbiology, 2012)
Here the composition of total and active archaeal communities in a sediment core of Jiulong River estuary at Fujian Province, Southern China was reported. Profiles of CH4 and SO42- concentrations from the sediment core indicated the existence of a sulfate-methane transition zone (SMTZ) in which sulfate reduction-coupled anaerobic oxidation of methane occurs. Accordingly, three sediment layers (16-18.5 cm, 71-73.5 cm, 161-163.5 cm) from the 1.2 m sediment core were sectioned and named top, middle and bottom, respectively. Total DNA and RNA of each layer were extracted and used for clone libraries and sequence analysis of 16S rRNA genes, the reverse transcription (RT)-PCR products of 16S rRNA and methyl CoM reductase alpha subunit (mcrA) genes. Phylogenetic analysis indicated that archaeal communities of the three layers were dominated by the Miscellaneous Crenarchaeotal Group (MCG) whose ecological functions were still unknown. The MCG could be further divided into seven subgroups, named MCG-A, B, C, D, E, F and G. MCG-A and MCG-G were the most active groups in the estuarine sediments. Known anaerobic methanotrophic archaea (ANMEs) were only found as minor components in these estuarine archaeal communities. This study, together with the studies of deep subsurface sediments, would be a very good start point to target and compare the specific active archaeal groups and their roles in the dark, deep subsurface sediment environments.